Impact of compliance with infection management guidelines on outcome in patients with severe sepsis: a prospective observational multi-center study. - Bloos, F.; Thomas-Ruddel, D.; Ruddel, H.; Engel, C.; Schwarzkopf, D.; Marshall, J. C.; Harbarth, S.; Simon, P.; Riessen, R.; Keh, D.; Dey, K.; Weiss, M.; et al. (Crit Care, 2014)
INTRODUCTION: Current sepsis guidelines recommend antimicrobial treatment (AT) within one hour after onset of sepsis-related organ dysfunction (OD) and surgical source control within 12 hours. The objective of this study was to explore the association between initial infection management according to sepsis treatment recommendations and patient outcome. METHODS: In a prospective observational multi-center cohort study in 44 German ICUs, we studied 1,011 patients with severe sepsis or septic shock regarding times to AT, source control, and adequacy of AT. Primary outcome was 28-day mortality. RESULTS: Median time to AT was 2.1 (IQR 0.8 - 6.0) hours and 3 hours (-0.1 - 13.7) to surgical source control. Only 370 (36.6%) patients received AT within one hour after OD in compliance with recommendation. Among 422 patients receiving surgical or interventional source control, those who received source control later than 6 hours after onset of OD had a significantly higher 28-day mortality than patients with earlier source control (42.9% versus 26.7%, P <0.001). Time to AT was significantly longer in ICU and hospital non-survivors; no linear relationship was found between time to AT and 28-day mortality. Regardless of timing, 28-day mortality rate was lower in patients with adequate than non-adequate AT (30.3% versus 40.9%, P < 0.001). CONCLUSIONS: A delay in source control beyond 6 hours may have a major impact on patient mortality. Adequate AT is associated with improved patient outcome but compliance with guideline recommendation requires improvement. There was only indirect evidence about the impact of timing of AT on sepsis mortality.
Keywords: Aged; Cohort Studies; *Disease Management; Female; Guideline Adherence/*standards/trends; Humans; Longitudinal Studies; Male; Middle Aged; Practice Guidelines as Topic/*standards; Prospective Studies; Sepsis/*diagnosis/*therapy